CHALLENGES AND SOLUTIONS IN LANGUAGE ACQUISITION AT THE PRIMARY EDUCATION LEVEL - Shaira Ismailova Ferdausovna (Modern American Journals, 2025)
Language learning in primary education is essential for children’s academic and social development. However, many young learners face common difficulties in learning vocabulary, grammar, pronunciation, and communication. These problems can be linked to factors such as lack of exposure, low motivation, limited home support, and large class sizes. This article discusses the main challenges faced by primary school students when learning a language and suggests modern, evidence-based teaching solutions. The paper highlights strategies like task-based learning, storytelling, scaffolding, and integrated skill instruction that help improve communicative competence and learner confidence.
Keywords: Language acquisition, primary education, early learners, language challenges, teaching solutions, task-based learning.